Bicara Perwira injects appreciation to police - Nor Salwana, Mohammad Idris (2022)
KUALA LUMPUR, 12 August 2022 - The Bicara Perwira programme titled ‘Police Sacrifice Against Communist Terrorists’ organised by Universiti Malaysia Pahang (UMP) in collaboration with the Royal Malaysia Police (RMP) recently took place at the Sultan Ahmad Shah Hall, RMP College Kuala Lumpur successfully injected appreciation among the young people to the struggle of the police in defending the beloved country.